COMPARISON OF TRADITIONAL- AND CASE-BASED METHOD FOR LEARNING PHYSIOLOGY AMONG 1ST YEAR MBBS STUDENTS - PRAMILA T; RAMAKRISHNA BANDARU; PRATHIBHA T; SURENDRA BV (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The medical science of physiology is both basic and applied. Traditional physiology instruction is teacher-centered, with little involvement from the students. A self-directed learning strategy focused on training through the use of personal narratives is known as case-based learning (CBL). The present study was conducted to assess the effectiveness of CBL method in teaching physiology among 1st year MBBS students. Methods: This study was conducted among 1st year MBBS students of 2022–2023 batch. The study design included a pre-test, a CBL discussion on a specific topic, and a post-test following the CBL session. MS Excel and SPSS version 23 were used to gather, tabulate, and statistically analyze the data. Results from the pre-and post-tests were compared using the student’s “t” test, and p<0.05 was regarded as statistically significant. The 12 questions that made up the feedback survey were all expressed as percentages. Results: When pre-and post-test results were compared, the post-test score after the CBL session was significantly better than the pre-test score of the session. The majority of students supported CBL activities. In student feedback, more than 95% of the students thought CBL classes helped interaction among them. More than 94% of the students thought CBL classes helped in clearing doubts, helped in increasing interest. More than 91% of the students thought CBL classes improved conceptual thinking. Conclusion: Through active learning, CBL can be utilized as an addition to lectures to augment standard teaching/learning approaches. It encourages the drive to learn and the development of clinical reasoning